Photometric observations of six asteroids carried out in Simeiz in 2002 - N. M. Gaftonyuk; Yu. N. Kruglyy (Вісник Астрономічної школи, 2004)
The photometric observations of six asteroids observed in Simeiz Observatory in 2002 are presented. The lightcurves of four near-Earth asteroids (1036 Ganymed, 6455 1992 HE, 31669 1999 JT6, 2002 HU11) and two main-belt asteroids (6317 Dreyfus and 22338 1992 LE) were obtained.